Phosphorus ingestion improves oral glucose tolerance of healthy male subjects: a crossover experiment - Khattab, May; Abi-Rashed, Christelle; Ghattas, Hala; Hlais, Sani; Obeid, Omar (Nutrition journal, 2015)
Fasting serum phosphorus (P) was reported to be inversely related to serum glucose and insulin, while the impact of P ingestion is not well documented. The effect of P intake with or before glucose ingestion on postprandial glucose and insulin statuses was investigated. Two cross over experiments using healthy male subjects were conducted. Experiment 1: Overnight fasted subjects (n = 7) randomly received: 500 mg of P tablets, glucose (75 g) solution with placebo or 500 mg of P tablets. Experiment 2: Overnight fasted subjects (n = 8) underwent similar procedures to those of experiment 1, except that placebo or 500 mg P tablets were given 60 min prior to glucose ingestion. In both experiments, serum P decreased following glucose ingestion. Co-ingestion of P with glucose improved, at time 60 min, postprandial glucose (P < 0.05), insulin (P < 0.05), and insulin sensitivity index (p < 0.006), while P pre-ingestion failed to exert similar effect. This study suggests that postprandial glucose and insulin are affected by exogenous P supply, especially when co-ingested with glucose.